Air flow profile evaluation around moving vehicle - Nalathambi, Deenesh Kumar (2014)
Highway lighting at night does increase the electricity costing because despite using solar energy to generate the electric for the lighting, mostly still uses direct current to work. The purpose of this study is to evaluate the air flow dispersed around moving vehicles and the wind turbine selection in harnessing electricity from the air flow dispersed. Solidworks and ANSYS software were used in modeling the vehicles and to analyze the flow characteristic, respectively. Analyses were done by the selection of 3 different vehicles which are a sedan car, a MPV and a bus by considering 3 different velocities i.e. 80km/h, 100km/h and 120km/h at 2 different environments which are the open road highway and road tunnel. Simulation computed the velocity field of the flow around the vehicles and also the turbine. The maximum wind speed dispersed obtained were used to calculate the wind power and mechanical power of the turbine analytically. It proves that the increment of vehicle’s speed increases the wind speed dispersed thus increasing the power generated by the selected wind turbine, Savonius Vertical Axis Wind Turbine with Two Semicircular blades.